2012
DOI: 10.1161/atvbaha.112.248344
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Angiotensin-Converting Enzyme and Activation of the Renin–Angiotensin System Contribute to 20-Hydroxyeicosatetraenoic Acid–Mediated Endothelial Dysfunction

Abstract: Objective 20-HETE promotes endothelial dysfunction by uncoupling eNOS, stimulating O2− production and reducing NO bioavailability. Moreover, 20-HETE-dependent vascular dysfunction and hypertension are associated with upregulation of the renin-angiotensin system (RAS). This study was undertaken to examine the contribution of RAS to 20-HETE actions in the vascular endothelium. Methods and Results In endothelial cells, 20-HETE induced ACE mRNA levels and increased ACE protein and activity by 2-3-fold; these eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
66
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(71 citation statements)
references
References 57 publications
2
66
0
Order By: Relevance
“…26 In addition, 20-HETE promotes the expression of the endothelial ACE, thus favoring the formation of the prohypertensive angiotensin II. 21,22 We and others have shown that disruption of the Cyp4a14 gene in mice results in androgen-dependent hypertension due to increased Cyp4a12 expression and 20-HETE biosynthesis in Cyp4a14KO male mice. 17 Increased expression of the sodium-hydrogen exchanger NHE3 and increased fluid reabsorption in proximal tubules contribute to the Cyp4a14KO hypertensive phenotype, 27 although endothelial nitric oxide synthase uncoupling, increased oxidative stress, and consequent vasoconstriction have been also postulated as a major cause of hypertension in these mice.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…26 In addition, 20-HETE promotes the expression of the endothelial ACE, thus favoring the formation of the prohypertensive angiotensin II. 21,22 We and others have shown that disruption of the Cyp4a14 gene in mice results in androgen-dependent hypertension due to increased Cyp4a12 expression and 20-HETE biosynthesis in Cyp4a14KO male mice. 17 Increased expression of the sodium-hydrogen exchanger NHE3 and increased fluid reabsorption in proximal tubules contribute to the Cyp4a14KO hypertensive phenotype, 27 although endothelial nitric oxide synthase uncoupling, increased oxidative stress, and consequent vasoconstriction have been also postulated as a major cause of hypertension in these mice.…”
Section: Discussionmentioning
confidence: 98%
“…21,22 For this reason, we analyzed renal mRNA levels of renin, angiotensinogen, AT1a receptor, and ACE in nondiabetic and 24-week diabetic wildtype and Cyp4a14KO mice. Nondiabetic Cyp4a14KO mice showed higher levels of renin and angiotensinogen mRNA, but comparable levels of AT1a receptor and ACE mRNA levels compared with nondiabetic wild-type mice (Supplemental Figure 2, A-D).…”
Section: Increased Collagen Deposition and Glomerular Basement Membramentioning
confidence: 99%
“…Vascular ACE expression requires the use of both the somatic and germinal ACE promoter regions, and disruption in these locations results in changes to protein structure and localization (Bernstein et al, 2005;Shen et al, 2008). We have recently identified 20-hydroxyeicosatetraenoic acid (20-HETE) as a potent inducer of endothelial ACE (Cheng et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both share several characteristics, as each has been shown to promote constrictor stimuli, smooth muscle proliferation and migration, increases in proinflammatory cytokines and chemokines, production of reactive oxygen species, enhanced expression of adhesion molecules, and arterial remodeling in hypertension (4,21,25,34). Our recent study identified 20-HETE as a potent inducer of endothelial angiotensin-converting enzyme (ACE), a critical enzyme involved in the production of the ANG II (3,6,30), suggested a close functional crosstalk between these two autacoids in the regulation of blood pressure and vascular function. To this end, experimental models of hypertension that show increased vascular 20-HETE production, such as the spontaneously hypertensive rats (SHR) (7) and androgen-induced hypertension (27,35,37), are also ANG II-mediated.…”
mentioning
confidence: 99%